Internalisasi Pendidikan Agama Islam Dalam Mewujudkan Pendidikan Karakter Disiplin Dan Cinta Damai Pada Siswa Kelas V MI Nurul Hidayah Sidorejo Sugio Lamongan - Riantini, Wahyu Tri; Habibah, Sulhatul (Fakultas Agama Islam, 2025)
This study discusses the lack of bad behavior and ethics of students such as truancy, late entry to school, neglect of homework (homework), not wearing a full uniform, physical violence, harassment, fights between students are factors that cause the problem of lack of discipline in students in the school environment. The objectives of this research are (1) to find out how to educate students' character of discipline and peace-loving (2) to know Islamic religious education in realizing discipline and peace-loving character education, (3) to know the inhibiting and supporting factors of discipline and peace-loving character education. The method used in this study is qualitative descriptive with data collection in the form of observations, interviews, and documentation. And the data analysis used is data reduction, data presentation, and conclusion drawn. research shows that (1) Educating students for discipline and peace-loving, especially forming discipline and peace-loving in students, has been done such as reading the Quran in the morning, istighosahan on Friday, and praying in congregation. The form of a peace-loving personality includes caring for others, mutual respect and tolerance, being friends with anyone regardless of race and ethnicity, (2) Islamic religious education in realizing discipline and peace-loving character education is basically Islamic religious education is very closely related to discipline and peace-loving character education through moral teachings and habits and compliance with regulations, (3) inhibiting and supporting factors for discipline and peace-loving character education, Factors inhibiting the formation of discipline and peace-loving character are students often skipping school. Meanwhile, the supporting factors are the celebration of the Prophet Muhammad's Birthday, the Qur'anic tartil reading competition using the yanbua method, the commemoration of August 17, 1945, and the annual endusanah event.